COMPARATIVE ANALYSIS OF ERNEST HEMINGWAY AND UZBEK LITERATURE - Atadjanova, Sevara (Журнал иностранных языков и лингвистики, 2023)
Our article looks at the development of this area in literature and literary criticism in general. Literature is the wealth of a person's spiritual world; it is impossible to be indifferent to it. However, as a part of literature, translation is a product of creative labor and national importance.